If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 2) = 5 + -3(3X + 5) Reorder the terms: 5(2 + x) = 5 + -3(3X + 5) (2 * 5 + x * 5) = 5 + -3(3X + 5) (10 + 5x) = 5 + -3(3X + 5) Reorder the terms: 10 + 5x = 5 + -3(5 + 3X) 10 + 5x = 5 + (5 * -3 + 3X * -3) 10 + 5x = 5 + (-15 + -9X) Combine like terms: 5 + -15 = -10 10 + 5x = -10 + -9X Solving 10 + 5x = -10 + -9X Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5x = -10 + -10 + -9X Combine like terms: 10 + -10 = 0 0 + 5x = -10 + -10 + -9X 5x = -10 + -10 + -9X Combine like terms: -10 + -10 = -20 5x = -20 + -9X Divide each side by '5'. x = -4 + -1.8X Simplifying x = -4 + -1.8X
| -5+96606069=14-x | | 7x+35=-28 | | 3(2l+4)=78 | | 9/6=3/n | | 2a+b-c=x | | 2+a=-3 | | 14-2x=14x-10 | | X^2/(3600-50x) | | 1/2=(4p)^-1/4 | | (13x3)-3)/3 | | 11X-17=9X+2 | | 4x-2y=58 | | 6+7x=3x+34 | | 10r^2=-12r+5 | | .75(z+2)=12 | | 16(3/4x-2)=8x | | 2/3x-3/4=1/6x=21/4 | | (q-4)*5=35 | | 7(x-5)=6(x+8) | | 0.52=logx | | -5X^2-11X+8=0 | | 4/x-45/x^2=-1 | | 5=c/-12 | | 1.50*430= | | x^2+13=77 | | 9w^2-16d^2=0 | | -4(z+3)-4(5-4z)= | | 3n^2=-26n-48 | | Y=(2/7)x-1 | | 8f-3g+2f-6g=10f-3g | | 16y=72+7y | | X^2-5x-3=2x-5 |